Analisis Laporan Keuangan Sebagai Penilaian Kinerja Keuangan PT Indofood Sukses Makmur Tbk - Imma Rokhmatul Aysa (Institut Agama Islam Tribakti Kediri, 2023)
Indofood Sukses Makmur Tbk is one of the largest companies in Indonesia in the food industry with its business units engaged in food management. The rapid development of PT Indofood Sukses Makmur's business activities certainly requires investors and creditors as a source of funding. Both need to analyze the company's financial statements as a reference source of company financial health information. Based on the financial reports of PT Indofood Sukses Makmur Tbk for the period 2018 to 2022 there has been an increase in fluctuations even though in 2020 to 2021 Indonesia was hit by the covid 19 pandemic. This type of research is quantitative descriptive research with data sources of PT Indofood Sukses Makmur's financial reports as of December 31 of the year 2018 to 2022. The first result, the assessment of the financial performance of PT Indofood Sukses Makmur based on analysis of liquidity ratios using the current ratio, obtained that the value of the current ratio from 2018 to 2022 experienced fluctuating conditions but was still in the very good category, namely above number 1. Second, the results solvency ratio analysis using the Debt to Asset ratio (DAR), it was found that the DAR values ​​from 2018 to 2022 were in the very good category, namely proficient under number 1. Third, profitability ratio analysis using the Return of Equity (ROE) ratio, it was found that the ROE value from 2018 to 2022 experiencing fluctuating conditions but still in the efficient category.